A Simple 13C NMR Method for the Discrimination of Complex Mixtures of Stereoisomers: All Eight Stereoisomers of α‐Tocopherol Resolved. Issue 11 (18th September 2015) - Lankhorst, Peter P.; Netscher, Thomas; Duchateau, Alexander L. L.
Abstract A simple one‐dimensional 13C NMR method is presented to discriminate between stereoisomers of organic compounds with more than one chiral center. By means of this method it is possible to discriminate between all eight stereoisomers of α‐tocopherol. To achieve this the chiral solvating agent (S)‐(+)‐1‐(9‐anthryl)‐2, 2, 2‐trifluoroethanol and the compound of interest were dissolved in high concentrations in chloroform‐d, and the nuclear magnetic resonance (NMR) spectrum was recorded at a low temperature. The individual stereoisomers of α‐tocopherol were assigned by spikes of the reference compounds. The method was also applied to six other representative examples. Chirality 27:850–855, 2015. © 2015 Wiley Periodicals, Inc.